Kajian Hubungan Keberadaan Infrastruktur Jalan Tol Cipali (Cikopo- Palimanan) terhadap Jumlah Aktivitas Ekonomi di Kabupaten Cirebon - Ryansyah Izhar; Muh Abdi Danurja Rahman Aziz (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Cipali Toll Road Infrastructure (Cikopo – Palimanan) was inaugurated in 2015 precisely on June 13, 2015. The existence of the Cipali Toll Road is believed to grow economic activity in the area near the toll gate (exit toll). The research aims to find out the relationship of the toll road to the amount of economic activity in Cirebon Regency. The method used in this study is the Hotspot Analysis method where it is used to show the concentration of locations of economic activity and the Geographically Weighted Regression (GWR) method to see the relationship of factors that are believed to increase economic activity in the area around the toll gate. Based on the results of the analysis, the amount of economic activity in the Study District is influenced by the Cipali Toll Road and other variables such as, 1) The number of residents, , 2) Access scores to the activity center, 3) The number of facilities, 4) The number of buildings and 5) The number of productive age communities in each sub-district in the study area.